Heat transfer and pressure loss analysis of a novel colloidal suspension in turbulent flow conduits / Sivanesh Kumar Selearajen - Sivanesh Kumar , Selearajen (2019)
The common working fluid in a heat exchanger can be identified as oil, water and ethylene glycerol. These fluids exhibit advantages in terms of ease of handling, recycling and disposing. Besides that, it has a low market price. Despite the advantages listed, these fluids are exhibits low thermal properties. Moreover, characteristic such as fouling and low total surface energy makes the overall heat transfer performance low resulting in the design of heat exchanger to be larger so that desired energy can be harnessed for the operations in the time duration. Nanofluid has been identified as a substitute to water and oil as a working fluid in the heat exchanger. There were attempts done to incorporate it into the industry. Graphene based nanofluid is found to be having significant thermal conductivity increase compared to other nanofluid. Thus, this study focuses on the acid treated GNP that has a better dispersion to flow in circular and square tube. The heat transfer ability of both the scenario is measured by the average heat transfer coefficient and Nusselt Number.